Low-intensity pulsed ultrasound attenuates replacement root resorption of avulsed teeth stored in dry condition in dogs - Saemi Seong (Nature Portfolio, 2021)
Abstract This study aimed to investigate the effects of low-intensity pulsed ultrasound (LIPUS) on replacement root resorption after replantation of avulsed teeth stored in a dry condition in dogs. A total of 73 premolar roots from four male mongrel dogs were intentionally avulsed with forceps and divided into four groups—HN, HL, DN, and DL—according to storage conditions and whether or not they received LIPUS treatment. Thirty-eight roots were kept in Hanks’ Balanced Salt Solution for 30 min (HN and HL groups), whereas the remaining 35 roots were left to dry in the air for an hour (DN and DL groups) prior to replantation. Following replantation, the roots in the HL and DL groups (21 and 18 roots, respectively) received a 20-min daily LIPUS treatment for 2 weeks. The animals were euthanized 4 weeks after the operation. Micro-computed tomography images were acquired for each root and the amount of replacement root resorption was measured three-dimensionally. Histological assessments were also carried out. There was significantly less replacement root resorption for the roots in the DL group compared to the DN group (p < 0.01). Histological findings in the DN group demonstrated evident replacement root resorption, whereas the DL group revealed less severe resorption compared to the DN group. Within the limitations, these results suggest that LIPUS could attenuate the replacement resorption of avulsed teeth stored in a dry condition, thereby improving their prognosis.